The Role of Social Media in Organizational Management: An Interview-Based Perspective - Majchrzak, Piotr (Rola mediów społecznościowych w zarządzaniu organizacjami: perspektywa oparta na wywiadach, 2024)
Aim: Nowadays, as the pace of life has accelerated, social media has become an essential tool for communication and social interaction. This trend applies not only to personal life but also to the workplace. The study aims to identify the role of social media in the context of organizational management from the perspective of enterprise employees. Methodology: Individual in-depth interviews with four respondents, who were representatives of different organizations, were used to conduct the research. Respondents were selected using purposive selection. The selection criteria were to work in a managerial position in a Polish small or medium-sized organization. Results: The study’s results indicated that social media is a flexible tool that can be easily adapted and used to benefit a company in many activities. Respondents indicated that the companies they work for use various social media such as Facebook, Instagram and LinkedIn. In addition, the research also pointed to the unique use of social media to organize knowledge within an organization. Implications and recommendations: The research included in this paper provides an employee perspective on social media used in Polish companies and identifies ways of using social media to manage an organization. Further research is indicated to expand research on the use of social media for organizing knowledge within an organization. However, issues related to company data security when using social media should also be considered. Originality/value: The value of this research is to highlight the use of social media by Polish organizations, not only in the area of marketing or employee search but also as a place to gather and organize knowledge.
Business Informatics = Informatyka Ekonomiczna, 2024, Nr 1-2 (67-68), s. 55-63
Keywords: social media; organizational management; marketing campaigns; social platforms; media społecznościowe; zarządzanie organizacją; kampanie marketingowe; platformy społecznościowe